Effect of potassium nitrate, gibberellic acid, and indoleacetic acid on seed germination of Andean blueberry (Vaccinium meridionale Swartz) - Magnitskiy, Stanislav V.; Ligarreto, Gustavo A. (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
The Andean blueberry is a South American wild plant with a high exportation potential among all eatable fruits for national and international markets. The current research was undertaken to evaluate the effects of potassium nitrate, gibberellic acid, and indoleacetic acid on the seed germination of this specie. Results showed that seeds stored inside fruits for a month or extracted from fruits presented 70 or 82% viability, respectively, and 29 or 38% germination at day 35. The imbibition of seeds in the solutions of 200-500 mg·L-1 potassium nitrate or gibberellic acid, increased the germination percentage on 32% (extracted seed storage), and 31 or 38% (seeds stored inside fruits), respectively, as compared with control treatment, whereas the treatments with indoleacetic acid did not have a significant effect on the germination. The results indicated that seeds of Andean blueberry are characterized by some mechanisms of seed dormancy.